P-O09 Development of a non face-to-face pre-operative assessment pathway for laparoscopic cholecystectomy. (16th December 2021) - Michel, Martin; Saab, Ala; Kronberga, Madara; Bonner, Clare; Fifer, Helen; Moran, Emily; Hammett, Felix; Saha, Arin
Abstract: Background: The Covid-19 pandemic has led to markedly reduced capacity in almost all areas of normal face-to-face activity in our hospitals. Prior to the pandemic, the standard pre-operative pathway for all patients included an initial appointment in the outpatients clinic and formal examination before recommending surgery. With the reality of limited clinic capacity, our unit developed a non face-to-face assessment pathway alongside a parallel green operating area in our local Independent Sector (IS) hospitals for laparoscopic cholecystectomy. This study describes and methodology and outcomes of this approach Methods: A non face-to-face (telephone) proforma for all new referrals for consideration of laparoscopic cholecystectomy was prepared in April 2020 with the first operations carried out in June 2020. All consultations were carried out by consultant surgeons and included thorough history, careful documentation of previous surgery and duration of symptoms and, where appropriate, patients were told to send images of their abdominal wall if they were unable to describe their scars. The first stage of the consent process was completed at initial appointment and all patients were sent written information about surgery. Patients who had BMI<40, uncomplicated biliary disease (biliary colic, mild cholecystitis, ERCP for CBD stones) and ASA of 1/2 were deemed suitable for surgery in the IS and sent across accordingly. A telephone pre-assessment was completed by the hospital and patients were sent blood tests forms in the post, as well as a Covid test to be completed at home followed by a period of self isolation before surgery. All patients were examined on the day of surgery by the operating surgeon and formal consent taken on the day. Primary outcomes that were recorded were cancellation on the day, transfer to the NHS hospital after surgery and complications. Results: From June 2020 to December 2020, when the contract with the IS changed, 218 patients attended the IS hospitals for planned elective laparoscopic cholecystectomy. Four patients (2%) did not have surgery (one cancelled as inappropriate for the Independent Sector, two patients whose Covid swab result was not complete and one patient who no longer wished to have surgery). Three patients required transfer to the NHS hospital for post-operative care (drains inserted after unanticipated difficult surgery). All patients were given details of the surgical SDEC unit at the NHS hospital to allow ease of admission in the event of any problems or complications. 28 patients (13%) attended SDEC within 30 days after surgery; most had blood tests and clinical assessment alone. One patient (<1%) required re-laparoscopy for abdominal pain three days after their initial surgery (washout alone) and 5 patients developed umbilical wound infections after surgery (antibiotics alone). Two patients were found to have CBD stones on MRCP. The waiting time from initial assessment to surgery for patients on this pathway was less than 18 weeks for 168 patients though patients who were not suitable for the Independent Sector have had waiting times that are considerably longer. Conclusions: These results demonstrate that it is possible to plan surgery for laparoscopic cholecystectomy without a face-to-face appointment at all which has considerable implications for resource allocation in the future; indeed, this approach has been continued within our unit even as clinic capacity has increased and been rolled out to patients with inguinal or para-umbilical hernia. Use of a green site away from the acute NHS hospital allowed elective surgery for non-urgent pathology to continue with acceptable waiting times even during the worst of the Covid-19 pandemic though patients who were not suitable have had markedly worse experiences and waiting times.